The linguistic, conceptual, and pragmatic challenges of communicating Galatians 3:1-14 in Chewa - Ernst Wendland (Acta Theologica)
The aim of this study is, first of all, to present a rhetorically oriented analysis of the central pericope of 3:1-14, with special reference to its pertinent oral-aural qualities. This forms the basis, in turn, for a comparative analysis of how this passage has been translated into Chewa in an old missionary-produced version (1922) in contrast to a more recent meaning-centered rendering (1998) as well as a special oral-poetic translation that was prepared as part of this study. Further attention is devoted to some of the conceptual challenges that this text, as an example of the Galatian epistle as a whole, poses for mother-tongue speakers due to their lack of an adequate biblical and hermeneutical frame of reference. Suggestions are offered as to how this significant cognitive disparity might be overcome through the use of a judicious selection of paratextual features, in particular, the incorporation of contextually relevant explanatory footnotes.